Recaudación tributaria municipal y calidad de los servicios públicos en la provincia de Loreto - Nauta año 2022 - Peña Mozombite, Patricia (2023)
The objective of this study is to determine the relationship between municipal tax collection and the quality of public services in the Province of Loreto - Nauta, year 2022, I opted for a type of applied study, descriptive level - correlational and non-experimental design; I include as population and sample 349 taxpayers; A technique that was the survey and the questionnaire was used as an instrument for data collection. After the verification of the results, it was established that the municipal tax collection is qualified as regular (25%), this is because the municipality sometimes requires the organizers of public events to pay the tax that corresponds to them, in addition, sometimes there is a specific staff to carry out the respective collection, likewise, the quality of public services on average (26%) since the public cleaning service in said province is never permanent; also, public roads are sometimes in continuous maintenance for better conservation; Likewise, there are rarely enough sports and recreational spaces for the development of sports activities. Finally, there is a significant relationship between municipal tax collection and the quality of public services; which has been contrasted by a coefficient of 0.754 and a significance of 0.000.